Cladding mode coupling suppression in hole-assisted fiber Bragg gratings - Han, Young-Geun; Lee, Young Jun; Kim, Gil Hwan; Cho, Hung Su; Lee, Ju Han; Lee, Sang Bae (WILEY, 2007)
We experimentally investigate the cladding mode coupling loss of fiber Bragg gratings written in hole-assisted fibers. The cladding mode coupling loss is remarkably suppressed due to air holes inside of the silica cladding. The reduction of cladding mode coupling loss of less than similar to 0.33 dB is obtained. The wavelengths spacing between the main peak due to the core mode coupling and the first side peak due to the first order cladding mode coupling is changed by the increase of the air holes size since the effective index of cladding mode is reduced by the air hole size within the fiber. The variation of the wavelength spacing is ranged from 2.0 to 2.28 nm. (c) 2006 Wiley Periodicals, Inc.